Vicky Pericleous, 'Economies of Empathy & Sustainability: a gestural return in the contexts of art' in the context of EMPACT|Empathy & Sustainability: The Art of Thinking like a Mountain, Creative Europe Program - Pericleous, Vicky (My University, 2024)
'This presentation, within the EMPACT European Program (Empathy and Sustainability: The Art of Thinking like a Mountain), expands on a set of speculative investigations and practices I have been researching into and developing through the years that respond to today’s themes. These connect with, as well as examine quests around the subject of 'Economies of Empathy & Sustainability: a gestural return in the contexts of art.' To expand on a series of relative critical stances, I would talk about the present and talk about the ongoing Series: Exoticisms and Other Acts, 2006 – today, which has been presented in many art venues, amongs them, Monodrome, the 3rd Athens Biennale, 2011–2012 at Diplareios School, Athens, Greece, curated by Nicolas Bourriaud, XY (Xenia Kalpaktsoglou and Poka-Yio) and ‘Rooms to Contemplate: Content and Perspective of a Collection’, 2017, at the Bank of Cyprus Cultural Foundation, curated by Savvas Christodoulides. Also I would shortly present as a following up to the above relevant contexts the work Also in Athens, 2019, shown in the international exhibition: ‘Art: Key to Conflict Resolution’ at Serafeio Municipal Centre, Athens, curated by Vasia Deliyianni, supported and co-hosted by Athens Culture Net of the City of Athens, an exhibition conceived as an extension of the relevant book launch at the Barnes Foundation, Philaderphia and in response to the book publication edited by Noam Lemelshtrich Latar, Jerry Wind and Ornat Lev-er... ...The initial printing materials used for both the works I have presented -products of an excess economic culture, which are mainly discarded after their vast circulation-, carry the burden of their specific socio-political conditioning. Their re-configuration into new speculative contexts could enable nonetheless, a shift towards other economies of making. Their gestural return into contexts of art, could open up potentialities for diverse modalities for engaging within the current states of our fragile worlds. Modalities that could perhaps produce and resonate new systems and tools which could move beyond hegemonic structures of power and authority in order to respond anew, to the complexities of today’s worlds. Ones that could point towards more vulnerable but decisive gestures of disturbance of the very power structures that have been producing inflexible constructs through the excess images and materials of our cultures. These -new- gestures of return, could reconnect and re-position these images and materials into other –conceivably more empathetic- contexts and perceptions.' Vicky Pericleous, artist/assistant professor (CUT)
Keywords: EMPACT; Empathy; Sustainability; Economies of Empathy; Performativities of the material; Construction of the imaginary; Narrative construction in the cultural landscape; Sociopolitical imaginaries; Distabilising hierarchies; Identity production & the image; Art practices & processes as means to cultural resilience & empathy